Application of various statistical approaches for sensory evaluation of seaweed dodol mixed agarwood infusion - I Gde Adi Suryawan Wangiyana; I Gusti Agung Ayu Hari Triandini; Idham Khalid (Journal of Agritechnology and Food Processing, 2025)
Seaweed dodol mixed agarwood infusion is an innovative culinary product from Lombok Island made primarily from seaweed flour. This research aims to conduct a sensory evaluation of seaweed dodol mixed agarwood infusion using the 9-point hedonic scale with different statistical approaches for the analysis. Four different seaweed concentrations were applied in this research as treatments: S1(seaweed flour 8% w/v), S2 (seaweed flour 10% w/v), S3 (seaweed flour 12% w/v), S4 (seaweed flour 14% w/v). The proximate analysis measures total protein, lipid, ash, water, and carbohydrates. This study used a Nine-point hedonic scale ranging from 9 (like extremely) to 1 (disklike extremely). Non-parametric statistics (Kruskal-Wallis and Freidman Test) and parametric statistics (ANOVA-CRD and ANOVA-RCBD) are the statistical approaches in this study, which are continued by DMRT (α = 0.05). Thirty trained respondents were evaluated based on appearance, aroma, taste, and texture. Proximate analysis shows that dodol has high moisture with medium carbohydrate content. The result shows that different statistical approaches have a consistent critical P-value, which shows the highly significant effect of treatment on the sensory evaluation value. DMRT analysis shows that the higher seaweed flour concentration results in a higher numerical hedonic value. The spider web chart shows respondents give a more sensitive evaluation of taste and texture than appearance and aroma. It could be concluded that different statistical approaches are reliable for analysing the significant effect of different seaweed flour concentrations on the sensory evaluation value of seaweed dodol mixed agarwood infusion.